Bridging the Gap Between UK Government Strategic Narratives and Public Opinion/Behavior: Lessons From COVID-19 - Dagnall, Neil; Drinkwater, Kenneth Graham; Denovan, Andrew; Walsh, R. Stephen (Frontiers in Communication, 2020)
In the UK, there exists an important “action gap” between Government advice on measures necessary to counter the threat of COVID-19, and the behavior of a significant minority of the population. There are several reasons for this disconnect, including lack of message potency (i.e., credibility and congruence), inflexible/habitual behavior patterns, prevailing beliefs (i.e., vulnerability to, and seriousness of COVID-19), and individuals valuing personal concerns above general public health. For official messages to be effective and advice adhered to, strong, coherent “strategic narratives” are required. This article, using a psychological perspective, critically examined prevailing COVID-19 UK Government announcements during the lockdown (23/03/2020) and initial easing phase (10/05/2020). Specifically, it focused on important communication inconsistencies, and identified factors that may facilitate and create barriers to the adoption of essential public health directives. This included deliberation of factors that enhanced source impact, diminished the influence of message content, and the negative consequences of contrary information. Accordingly, this article proposes a framework for providing a unifying strategic narrative on COVID-19, one that helps to maximize the impact of key messages and promote effective behavior change. This framework places an emphasis on engaging the full range of actors and considers ways of reducing the efficacy of false information. The article provides recommendations that will potentially improve the reception of government policy and suggests how strategic narratives can harness the drivers of behavioral change needed to meet challenges such as COVID-19.